Funeral and interment practices of rural residents: A mixed methods study. Issue 2 (7th February 2021) - Rainsford, Suzanne; Phillips, Christine B.; MacLeod, Rod D.; Wilson, Donna M.
Abstract: There are few studies on interment preferences and practices for people in remote and rural regions of developed countries. This mixed methods study in rural Australia collated data on funeral and interment practices with an ethnographic exploration of the post-death preferences of terminally-ill rural residents. In the region, between February 2015 and May 2016, 44% of decedents were cremated. Burial preferences reflected family traditions, generational connections to historic cemeteries, and the wish to instantiate belonging to people and place. Cremation provided the opportunity for ashes to be scattered at personally-significant places. Funeral planning was important for patients and family caregivers, and funerals are valued rural community rituals.